"AI Poet" in the Classroom: A Study on the Creative Teaching Model of Poetry in Primary and Secondary Schools Empowered by Technology (Journal of science and technology exploration, 2026)
Currently, poetry teaching in primary and secondary schools faces problems such as rigid teaching models, single teaching methods, and students' lack of emotional experience. To effectively address this dilemma, this study proposes a creative teaching model integrated with generative artificial intelligence (AI) technology. With "AI Poet" as an intelligent auxiliary tool, the core of this model lies in using natural language processing, virtual reality and other technologies to reconstruct the teaching process of "experience-interaction-creation" through approaches such as situational creation, virtual dialogue, intelligent analysis and poetic extension. Combined with the teaching practice case of Sending Yuan Er to Anxi, the study elaborates on the implementation methods and effects of this model. The results show that this model can effectively stimulate students' interest in poetry learning, promote the development of their innovative thinking and aesthetic ability, and drive the transformation of teaching objectives from knowledge transmission to core literacy cultivation. It provides a referential paradigm for the reform and innovation of poetry teaching in primary and secondary schools.
Keywords: AI poet; Poetry in primary and secondary schools; Creative teaching; Sending Yuan Er to Anxi